Electrochemically Generated Luminescence of Luminol and Luciferin in Ionic Liquids. Issue 1 (22nd December 2022) - Belotti, Mattia; El‐Tahawy, Mohsen M. T.; Darwish, Nadim; Garavelli, Marco; Ciampi, Simone
Abstract: Electrochemiluminescence (ECL) is the generation of light triggered by an electrochemical reaction. ECL has been extensively studied in solvent‐based electrolytes, but there is a lack of data on using electrode reactions to populate an excited‐state light emitter in room temperature ionic liquids (RTILs). This work explores the current response, light intensity (photon counting), and spectral signatures of the cathodic ECL of luminol and firefly's luciferin in imidazolium‐based RTILs. We have demonstrated that the cathodic (superoxide‐triggered) ECL of both luminol and adenylate‐ester of firefly's luciferin is viable in RTILs, explored the effect of water contaminations, and importantly, shown that the ECL signal persists for up to about 700 s after the removal of the external cathodic pulse, which is probably due to the stabilization of superoxide by double‐layer cation‐rich structures. Long‐lived RTIL double‐layer structures and their endogenous fields are detected as stable and discrete open‐circuit potential plateaus. Abstract : Long‐lived electrochemiluminescence : This work demonstrates long‐lived blue and red electrochemiluminescence (ECL) of luminol and firefly's luciferin in room temperature ionic liquids. Cathodically generated superoxide continues to elicit luminescence for up to 700 s after the removal of the cathodic bias, suggesting a link between superoxide stability and the stability of cation‐rich double layer structures in ionic liquids.